A Thick-Walled Organism Isolated from the Cockroach Gut by Using a Spent Medium Technique - Cruden, Diana Loeb (1980)
By using a conditioning technique whereby complex media are inoculated several times with bacteria from the hindgut of the cockroach Eublaberus posticus, a succession of bacterial types occurred. An obligately anaerobic, pleomorphic, thick-walled, gram-positive organism is described which was isolated by this culturing technique.